The Styling Process - Milburn,C; Childs,PRN (Professional Engineering Publishing, 2001)
The automotive sector is a mature market with the consumer having increasingly more choice and as a result a greater influence on the design of new products. This paper outlines the complexity of the design process, the importance of image and branding and suggests, using an example, a possible way forward to meet the needs of the sophisticated consumer. In particular the trend for consolidation in the automotive sector is challenged as an avenue for success in favour of a leaner design process to meet the timescales of consumer interest.